Frailty and suicidal ideation among older adults living alone in the community: a moderated mediation model of perceived burdensomeness and positive emotions - Yang, Yang; Zhang, Xinyue; Zhang, Dan; Su, Yonggang (Frontiers in Public Health, 2024)
Background Suicide rates among older adults individuals living alone in the community are comparatively high. The prevalence of suicidal ideation among older adults living alone in the community was assessed using the interpersonal-psychological theory of suicide and the broaden-and-build theory of positive affect. Objectives The research objectives of this study was examine to the prevalence of suicidal ideation among older adults living alone in the community. It was examined whether perceived burdensomeness mediated the relation between frailty and suicidal ideation, and whether positive emotions moderated either the indirect or direct effect of a mediation model. Methods The model was tested on 893 older adults people living alone in the community in Xintai City, China. An assessment of participants’ frailty, suicidal ideation, perceived burdensomeness, and positive emotions was conducted. Results The results demonstrated that perceived burdensomeness acted as a partly mediating factor in the relationship between frailty and suicidal ideation. In addition, the direct and indirect effects of the mediation model were moderated by positive emotions. When levels of positive emotion were high, fragility had a weaker effect on suicidal ideation, and perceived burdensomeness had a weaker effect on suicidal ideation. Conclusion Results emphasize that interventions aimed at improving positive emotions could have a protective effect on frail older people living alone in the community who are at risk of suicide.